Significance of five membered heterocycles in fine tuning of HOMO-LUMO gap of simple donor-acceptor system as organic solar cell material: A DFT approach. (2020) - Sherin, D.R.; Manojkumar, T.K.
Abstract: The significance of five membered heterocycles in simple donor-acceptor system was elaboratively studied by density functional theory (DFT) and time dependent density functional theory (TDDFT). By effectively substituting eight different rings the HOMO-LUMO gap can be reduced considerably. The nuclear independent chemical shift (NICS) calculations help to predict the aromaticity of central heterocyclic systems. The natural bond orbital (NBO) analysis reveals the charge contribution. The close observation of frontier molecular orbitals (FMO) gives a detailed explanation of delocalization.